2012
DOI: 10.1002/chem.201200702
|View full text |Cite
|
Sign up to set email alerts
|

Partially Reduced Graphite Oxide as an Electrode Material for Electrochemical Double‐Layer Capacitors

Abstract: Partially reduced graphite oxide was prepared from graphite oxide by using synthetic graphite as precursor. The reduction of graphite oxide with a layer distance of 0.57 nm resulted in a reduction of the layer distance depending on the degree of reduction. Simultaneously the amount of oxygen functionalities in the graphite oxide was reduced, which was corroborated by elemental analysis and EDX. The electrochemical activation of the partially reduced graphite oxide was investigated for tetraethylammonium tetraf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
37
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 57 publications
(40 citation statements)
references
References 77 publications
2
37
0
Order By: Relevance
“…For 17 "dehydrated" as well as reduced graphite oxide it is (001), corresponding to 6.2 Å, but it 18 gradually disappeared as we go from rGO1 to rGO8. In rGO3 and rGO8 a broad peak arose and 19 which also approached the position of the graphite (002) reflection, as previously observed [15]. 20 In rGO8 the interlayer distance was calculated to be 3.77 Å, a much smaller value that 21 approaches the spacing in natural graphite, namely 3.36 Å.…”
mentioning
confidence: 79%
See 2 more Smart Citations
“…For 17 "dehydrated" as well as reduced graphite oxide it is (001), corresponding to 6.2 Å, but it 18 gradually disappeared as we go from rGO1 to rGO8. In rGO3 and rGO8 a broad peak arose and 19 which also approached the position of the graphite (002) reflection, as previously observed [15]. 20 In rGO8 the interlayer distance was calculated to be 3.77 Å, a much smaller value that 21 approaches the spacing in natural graphite, namely 3.36 Å.…”
mentioning
confidence: 79%
“…We shall refer to these three kinds of powders as 12 rGO1, rGO3 and rGO8 respectively. 15 X-ray diffraction was performed in a Philips X'pert Pro using Cu Kα 1 radiation (λ=1.5406 Å) 16 at 0.017° steps over the range of 2θ from 5° to 50°, with the sample heated to 70°C at 10°C/min, 17 under vacuum. The diffractogram thus obtained at 70°C was refreshed every 5 min until no 18 further change was discernible.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
See 1 more Smart Citation
“…This decrease could be mainly attributed to the reduced NiO content, which decreased the number of redox sites available on the electrode. [13] The improvement in the electrochemical performance of NiO when grafted to the CDC surface can be attributed to the combined influence of different mechanisms, such as increased surface area (see Figure SI-B in the Supporting Information) and conductivity of the electrode overlay. This is predominated by the relative ability of electrons to jump the gap between closely spaced aggregates (electron tunneling), [45] and by graphitic conduction through aggregates in contact, as observed in other carbon composite systems.…”
Section: Influence Of Different Electrolytes and Carbon Contentsmentioning
confidence: 98%
“…Figure 1 compares the energy density and power density performances of some recent studies in which NiO has been used in combination with these nanostructured carbons as composite electrodes. [12][13][14][15][16][17][18][19][20][21][22][23] However, reports have shown that it is difficult to produce large-scale porous electrode areas when using graphene and CNTs. [24,25] Graphene sheets without proper surfactant tend to aggregate (causing reduction in the conductivity), which restricts the intervening pore volume for…”
Section: Introductionmentioning
confidence: 99%